Parenting Styles and Gadget Use: Examining hIntensity and Negative Impacts on Early Childhood Development in Bima City - Muliati, Meli; Hendra, Hendra; Ruslan, Ruslan (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study explores the influence of different parenting styles democratic, authoritarian, and permissive on the intensity of gadget use and its negative impacts on children aged 1-8 years in Bima City. Utilizing a mixed-methods approach, the research design included literature review, hypothesis formulation, data collection via online questionnaires, and data analysis. Quantitative data were analyzed using regression techniques, and qualitative data provided contextual depth. The findings reveal significant differences in gadget use intensity and associated negative outcomes, including reduced social skills and hearing problems, depending on parenting style. Democratic and authoritarian parenting were linked to higher gadget use, while permissive parenting exhibited a wide range of use patterns, from high usage to complete abstention. The study underscores the importance of effective parental monitoring and engagement to manage children's screen time and mitigate adverse effects. Limitations include a localized sample and reliance on self-reported data, suggesting the need for further research in diverse populations. These findings have important implications for parenting strategies and public health policies, emphasizing the need for targeted interventions to educate parents on managing children’s digital habits and promoting healthy development. Future research should further investigate these relationships and develop comprehensive support strategies for parents.